Randomised-crossover clinical trial on the substantivity of a single application of a gel containing chlorhexidine and o-cymen-5-ol on the oral biofilm and saliva - B. Suárez-Rodríguez; A. Regueira-Iglesias; T. Blanco-Pintos; A. Sánchez-Barco; N. Vila-Blanco; C. Balsa-Castro; M. J. Carreira; I. Tomás (BMC, 2024)
Abstract Background No clinical trials have evaluated the antimicrobial activity and substantivity of gel formulations containing chlorhexidine (CHX) and cymenol. Objective To compare the in situ antimicrobial effect and substantivity of a new 0.20% CHX + cymenol gel (test) with the current 0.20% CHX gel formulation (control) on salivary flora and dental plaque biofilm up to seven hours after a single application. Methods A randomised-crossover clinical trial was conducted with 29 orally healthy volunteers participating in the development of Experiments 1 (saliva) and 2 (dental plaque biofilm). All subjects participated in both experiments and were randomly assigned to receive either the test or control gels. Samples were collected at baseline and five minutes and one, three, five, and seven hours after a single application of the products. The specimens were processed using confocal laser scanning microscopy after staining with the LIVE/DEAD® BacLight™ solution. Bacterial viability (BV) was quantified in the saliva and biofilm samples. The BV was calculated using the DenTiUS Biofilm software. Results In Experiment 1, the mean baseline BV was significantly reduced five minutes after application in the test group (87.00% vs. 26.50%; p < 0.01). This effect was maintained throughout all sampling times and continued up to seven hours (40.40%, p < 0.01). The CHX control followed the same pattern. In Experiment 2, the mean baseline BV was also significantly lower five minutes after applying the test gel for: (1) the total thickness of biofilm (91.00% vs. 5.80%; p < 0.01); (2) the upper layer (91.29% vs. 3.94%; p < 0.01); and (3) the lower layer (86.29% vs. 3.83%; p < 0.01). The reduction of BV from baseline was observed for the full-thickness and by layers at all sampling moments and continued seven hours after application (21.30%, 24.13%, and 22.06%, respectively; p < 0.01). Again, the control group showed similar results. No significant differences between test and control gels were observed in either saliva or dental plaque biofilm at any sampling time. Conclusions A 0.20% CHX + cymenol gel application demonstrates potent and immediate antimicrobial activity on salivary flora and de novo biofilm. This effect is maintained seven hours after application. Similar effects are obtained with a 0.20% CHX-only gel.